Hubungan Kontrasepsi Hormonal, Pengetahuan Dan Sikap Tentang Cuti Haid Dengan Praktik Cuti Haid Pada Pekerja Perempuan PT. Nyonya Meneer Semarang - Setyaningsih, Yuliani; Purnami, Cahya Tri; Mahmudah, Mar Atul (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2008)
Background: According to state role on section 81 undang-undang No 13/2003 mentioned that woman workers who are suffering dismenorrhea during menstruations period could take leave on first and second day menstruation. However not all woman workers in PT.Nyonya Meneer Semarang utilize this policy. One of the reason is using hormonal contraception make their period unstable and irregular. The aim of this study was to analyze about relationships between hormonal contraception usage, knowledge and attitude about menstruation leave and the practice of menstruation leave.Method: This research was an explanatory, with a cross sectional approach. The sample recruited from woman workers of PT. Nyonya Meneer Semarang who have age less than 50 years, not menopause, and using hormonal contraception. 81 woman workers were involved in this study selected by simple random sampling. Chi-square test was employed to test significances between variables.Result: The study shows that there was a relationship between hormonal contraception usages with the practice. However, knowledge and attitude of woman workers have no relation with menstrual leave practice. This study suggest that the company should socialize about determination on menstruation leave and the effect to the woman workers in order to makethe woman workers utilize this rule.Keywords: hormonal contraception, rules of menstruation leave, women worker